2015
DOI: 10.1099/vir.0.000037
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the host range: mandarin fish is susceptible to a vesiculovirus derived from snakehead fish

Abstract: Members of the genus Vesiculovirus, which belongs to the family Rhabdoviridae, can cause great economic loss in fish culture. In the present report, a vesiculovirus [named snakehead fish vesiculovirus (SHVV)] was isolated from diseased hybrid snakehead fish. SHVV shared 94 % nucleotide sequence identity at the genomic level with Siniperca chuatsi rhabdovirus (SCRV), which infects mandarin fish (S. chuatsi). We showed that SHVV was able to replicate and proliferate well in SSN-1 cells, which originate from stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…SHVV was isolated and stored in our lab [ 20 ]. ZF-4 cells were obtained from Institute of Hydrobiology, Chinese Academy of Sciences (Wuhan, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SHVV was isolated and stored in our lab [ 20 ]. ZF-4 cells were obtained from Institute of Hydrobiology, Chinese Academy of Sciences (Wuhan, China).…”
Section: Methodsmentioning
confidence: 99%
“…The genome of SHVV consists of a negative, single-stranded RNA which encodes five viral structural proteins, including Nucleoprotein (N), Phosphoprotein (P), Matrix protein (M), Glycoprotein (G), large protein (L) or RNA dependent RNA polymerase [ 19 ]. Recently, we showed that Mandarin fish was susceptible to SHVV, indicating that SHVV might have broad host ranges [ 20 ]. Zebrafish ( Danio rerio ) has become an attractive research model for the studies of fish diseases.…”
Section: Introductionmentioning
confidence: 99%
“…During the preparation of this manuscript, the sequences of 5 strains of ITV were reported [70]. The authors suggested that ITV and BAGV should be considered a single species with 2 different clades representing "old isolates" and "recent isolates".…”
Section: Itv and Bagvmentioning
confidence: 99%
“…There has been considerable discussion concerning the significance of these observations [79] and the hypothesis that POW was introduced into North America using the Beringian land bridge that connected Asia and North America between 15,000-11,000 years ago has recently been used to estimate modelling the temporal origin and evolution of flaviviruses (see the discussion section) [85].…”
Section: A Timed Evolutionary Perspective For Old To New World Introdmentioning
confidence: 99%
See 1 more Smart Citation